VD_FINDINFO Jug / 2012 / 208 vom 22. März 2012 - VD Tribunal cantonal (2012)
INDEMNITÉEN GÉNÉRAL, DÉPENS, TORT MORAL | 429 al. 1 let. a CPP (CH), 429 al. 1 let. c CPP (CH), 429 al. 2 CPP (CH), 429 CPP (CH), 430 CPP (CH)